The non-intubated anesthesia for airway surgery - Okuda, Katsuhiro; Nakanishi, Ryoichi (Journal of Thoracic Disease, 2016)
Surgical treatment for lung cancer including airway resection following reconstruction is typically performed under general anesthesia with single-lung ventilation because it is necessary to maintain a sufficient working space and to adjust the airway pressure for the leak test. However, non-intubated thoracic surgery has been gradually developed in recent years for thoracoscopic surgery, due to its lower rate of postoperative complications, shorter hospitalization duration, and lower invasiveness than the usual single-lung anesthesia. Initially, only minor thoracoscopic surgery, including wedge resection for pneumothorax and the diagnosis of solitary pulmonary nodules, was performed under waking anesthesia. However, major thoracoscopic surgery, including segmentectomy and lobectomy, has also been performed under these conditions in some institutions due to its advantages with respect to the postoperative recovery and in-operating room time. In addition, non-intubated thoracic surgery has been performed for tracheal resection followed by reconstruction to fully explore the advantages of this surgical modality. In this article, the merits and demerits of non-intubated thoracoscopic surgery and the postoperative complications, perioperative problems and optimum selection criteria for patients for thoracic surgery (mainly airway surgery) are discussed.